ANALISIS KINERJA KEUANGAN SEBAGAI SALAH SATU DASAR PENGAMBILAN KEPUTUSAN INVESTASI - Niam, Fitriyatun (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2014)
The purpose of this research is to find out the financial performance of food and beverages companies which are listed in Indonesia Stock Exchange by using profitability, solvability ratio analysis, and EVA concept. Three companies which have been selected as the research object are PT.Cahaya Kalbar Tbk, PT.Prasidha Aneka Niaga Tbk, and PT.Sekar Laut Tbk during the years of 2008 â 2012. The method in this research uses qualitative research method since it does not test any hypothesis; the research is carried out by analyzing financial statements . Based on the result of research which has been carried out by using profitability and solvability ratio analysis show that the financial performance of these three companies are well. Nevertheless this calculation is not similar to the calculation result of EVA which shows that PT Cahaya Kalbar Tbk, and PT Prasidha Aneka Niaga Tbk, do not always have positive EVA value, while the EVA value of PT Sekar Laut Tbk tend to be negative. It can be concluded from the above discussion that by performing EVA and financial ratio analysis can be used as one of the foundations to make either the investment decision or financing both to potential investors and creditors. Keywords: Financial Performance, Profitability Ratio, Solvability Ratio, and EVA Concept